PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK (PjBL) UNTUK MENINGKATKAN KREATIVITAS SISWA - Ivy Yusika; Turdjai Turdjai (UNIB Press, 2021)
The purpose of this study was to describe the application of a project-based learning model (PjBL) to increase student learning creativity in 2D art subjects. The design used in this research is classroom action research (CAR). A total of 25 students consisting of 8 males and 16 females were the research respondents. Data collection techniques used observation sheets with 6 aspects observed, namely: showing extraordinary curiosity, creating a variety and number of ideas to solve problems, often proposing unique and smart responses, daring to take risks, like to try, and sensitive to beauty and aesthetics of the environment. The results of the study indicate that the application of the PjBL learning model can increase the creativity of class XI students at SMA Negeri 3 Lahat